Water absorption, friction and wear behaviors of polypropylene composites filled with hydroxyapatite - (:unkn) unknown (Trans Tech Publications Ltd, 2017)
In the present work, the friction and wear properties of Polypropylene (PP) based composites filled with Hydroxyapatite (HA) particles were studied. Fillers contents in the PP were 10, 20, and 30 wt%. The effects of hydroxyapatite ratio on the water absorption, friction and wear properties of the polymer composites is presented. The result showed that the addition of HA to the composite changed the water absorption, friction coefficient and wear rate. © 2017 Trans Tech Publications, Switzerland.
Keywords: Friction; Hydroxyapatite; Mechanical properties; Polypropylene; Wear